Interventions for improving metabolic risk in overweight Latino youth - Davis, Jaimie N (Blackwell Publishing Ltd, 2010)
This review highlights various components of interventions that reduced obesity and type 2 diabetes risk factors among overweight Latino youth. A total of 114 overweight Latino adolescents completed one of four randomized controlled trials: 1) strength training (ST; boys only); 2) modified carbohydrate nutrition program (N); 3) combination of N+ST; or 4) N + Combination of Aerobic and ST (N+CAST; girls only). Measures included: strength by 1-repetition max, dietary intake by 3-d records, body composition by DEXA/MRI, glucose/insulin indices by oral and IV glucose tolerance tests. ST improved insulin sensitivity by 45% in Latino boys, and N, N+ST, and N+CAST improved glucose control in Latino boys and girls. The CAST approach reduced all adiposity measures by ∼3% in Latina girls. Participants who decreased added sugar, increased dietary fiber, and had increased parental attendance, regardless of intervention group, improved insulin action and reduced visceral adipose tissue. In conclusion, ST, CAST, and a modified carbohydrate nutrition program with separate parental classes were all successful components of the interventions that decreased obesity and related metabolic diseases.